2019
DOI: 10.1021/acsanm.8b02243
|View full text |Cite
|
Sign up to set email alerts
|

Chemical-Vapor-Deposited Graphene as a Thermally Conducting Coating

Abstract: We performed scanning thermal microscopy measurements on single layers of chemical-vapor-deposited (CVD) graphene supported by different substrates, namely, SiO2, Al2O3, and PET using a double-scan technique to remove the contribution to the heat flux through the air and the cantilever. Then, by adopting a simple lumped-elements model, we developed a new method that allows determining, through a multistep numerical analysis, the equivalent thermal properties of thermally conductive coatings of nanometric thick… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…Indeed, different studies reported thermal conductivity values for pristine graphene between 2000 and 5000 W m -1 K -1 , depending on the measurement technique [9][10][11][12][13][14]. However, this outstanding heat conductivity is affected by several parameters, including defectiveness [12,15,16], lateral size [17], number of layers [9,18] and presence of wrinkles [11,19].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, different studies reported thermal conductivity values for pristine graphene between 2000 and 5000 W m -1 K -1 , depending on the measurement technique [9][10][11][12][13][14]. However, this outstanding heat conductivity is affected by several parameters, including defectiveness [12,15,16], lateral size [17], number of layers [9,18] and presence of wrinkles [11,19].…”
Section: Introductionmentioning
confidence: 99%
“…The determination of the thermal conductivity requires additional modelling, strong assumptions, and several calibration steps on reference samples [ 153 , 154 ]. Despite these difficulties, recent studies have successfully used the SThM technique to quantitatively determine the thermal conductivity of 2D materials, such as graphene [ 143 , 155 , 156 ]. However, SThM is considered to be ideal to investigate heat transport at nanoscale contacts and interfaces with sub-nW and sub-10 nm heat flux and thermal spatial resolution, respectively.…”
Section: Experimental Techniques For Thermal Characterizationmentioning
confidence: 99%
“…However, SThM is considered to be ideal to investigate heat transport at nanoscale contacts and interfaces with sub-nW and sub-10 nm heat flux and thermal spatial resolution, respectively. The SThM technique has been employed recently to investigate heat transfer in semiconductor nanostructures, e.g., nanowires [ 115 , 157 , 158 , 159 ], supported thin films [ 145 , 160 , 161 ] and 2D materials [ 142 , 143 , 144 , 146 , 148 , 154 , 155 , 156 , 162 , 163 ]. For instance, recently El Sachat et al [ 144 ] performed high-vacuum SThM measurements to experimentally probe the transition from ballistic to diffusive thermal transport in suspended single-layer graphene.…”
Section: Experimental Techniques For Thermal Characterizationmentioning
confidence: 99%
“…While nanoscale constrictions are of great importance for their electrical transport characteristics, particularly in the quantum regime [16,17], they also promote enhanced Joule self-heating and thermoelectric coefficients [18][19][20][21]. For such structures, scanning thermal microscopy [4] is an ideal tool to map surface temperatures with spatial resolution of a few nanometres, as applied to carbon nanotubes [22], nanowires [23][24][25][26] and 2D materials [20,21,[27][28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%